Multilocular Thymic Cyst with Superior Cava Vein Syndrome Complication - Widodo, Rahadi (Malang Respiratory Journal, 2019)
Background: Thymic cysts are uncommon, only comprising 1-3% of all mediastinal masses and 5-28% of the mediastinal cysts. Usually benign entities representing remnants of persistent thymopharyngeal duct or cystic degeneration of Hassall corpuscles. Unilocular thymic cysts are probably of congenital origin (derived from embryologic thymic tissue) and without inflammation, while multilocular thymic cysts are predominantly acquired, resulting from inflammation or neoplasm, have thick walls and contain dark-brown fluid.Case: A 51-year-old male with complaint of pain on his neck, shoulder, and right chest, accompanied with swelling of right arm and vena ecstasis on his neck and chest wall. The patient was diagnosed as anterior mediastinal tumor with complication vena cava superior syndrome. He underwent surgical treatment with approach median sternotomy and wide excision of tumor. Histopathologic examinaton of the tumor reveals a multilocular thymic cyst. Pneumonia occured after surgery and could be overcome by aggresive combination antibiotic treatment. There was right pleural effusion and right phrenic nerve paralysis after surgery. In this patient, also there is a mass in right posterior pleural cavity which has not been removed by surgical treatment.